2006
DOI: 10.1038/nchembio813
|View full text |Cite
|
Sign up to set email alerts
|

Ceruloplasmin is a NO oxidase and nitrite synthase that determines endocrine NO homeostasis

Abstract: Nitrite represents a bioactive reservoir of nitric oxide (NO) that may modulate vasodilation, respiration and cytoprotection after ischemia-reperfusion injury. Although nitrite formation is thought to occur via reaction of NO with oxygen, this third-order reaction cannot compete kinetically with the reaction of NO with hemoglobin to form nitrate. Indeed, the formation of nitrite from NO in the blood is limited when plasma is substituted with physiological buffers, which suggests that plasma contains metal-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
264
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 323 publications
(274 citation statements)
references
References 50 publications
7
264
1
1
Order By: Relevance
“…Approximately 80-90% of plasma nitrite is derived from endothelial nitric oxidase synthase derived nitric oxide [2]. Recently it has been shown that plasma cerulloplasmin has a nitric oxide oxidase activity, and may play a role in the conversion of nitric oxide to nitrite in vivo [3]. The nitrite anion, which is present between 0.2 and 10 ÎŒM in the blood and tissues [4,5], may represent a storage form of nitric oxide that is made available under conditions of oxygen deprivation to maintain cell survival.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 80-90% of plasma nitrite is derived from endothelial nitric oxidase synthase derived nitric oxide [2]. Recently it has been shown that plasma cerulloplasmin has a nitric oxide oxidase activity, and may play a role in the conversion of nitric oxide to nitrite in vivo [3]. The nitrite anion, which is present between 0.2 and 10 ÎŒM in the blood and tissues [4,5], may represent a storage form of nitric oxide that is made available under conditions of oxygen deprivation to maintain cell survival.…”
Section: Introductionmentioning
confidence: 99%
“…However, a small fraction of the NO is converted to a biologically active NO 2 -either by ceruloplasmin [18] or via NO autoxidation (Fig. 2).…”
Section: Classic L-arginine/no Synthase Pathwaymentioning
confidence: 99%
“…NO produced through this pathway has been proposed to represent a NOSindependent alternative to the classical pathway in which NO is produced by oxidation of L-arginine in a reaction catalyzed by NOS . Under normal physiological pH and oxygen tension, nitrite is an endogenous substance produced via the oxidation of NO (in cells by cytochrome C oxidase (Torres et al, 2000), in blood principally by ceruloplasmin; Shiva et al, 2006), and for many years nitrite was simply considered a relatively inert metabolic end-product of NO. However in the past decade, it has become apparent that under certain conditions nitrite exerts potent biological effects, and several research groups have identified that -particularly at low pH and oxygen tension -nitrite is reduced by various nitrite reductases to NO (Cosby et al, 2003;Webb et al, 2004;Rassaf et al, 2007;Shiva et al, 2007a;Feelisch et al, 2008;Webb et al, 2008a;Aamand et al, 2009;Totzeck et al, 2012a).…”
Section: Nitrite As a Potential Nitric Oxide Substitutementioning
confidence: 99%